An Utilizing Marginal Red Yellow Podzolic Soil as a Growing Medium for Auxin-Soaked Cutting Propagation of Red Master Grapes (Vitis vinifera L) - Pamungkas, Saktiyono Sigit Tri; Pramudya, Yudhi; Sukmawati, Fitria Nugraheni; Tusrianto, Tusrianto; Hanum, Farrah Fadhillah (Green Engineering Society, 2023)
Grape (Vitis vinifera) cultivation is hampered by a lack of suitable land and challenging nurseries. Use of crimson yellow podzolic soil for vine cuttings can be suboptimal. Although podzolic soil has a low capacity to absorb macro- and micronutrients and an acidic pH, it can nevertheless be used as a growing medium. A synthetic growth regulator (ZPT) bath of naphthalene acetic acid (NAA) needs to be added to the local red master grape variety, which has started to develop as a scion in nurseries. In order to assess the impacts of NAA-soaked concentrations on podzolic soil media and identify the morphological traits of local Red Master grape cuttings, this study set out to identify these traits. Its goal was to find out how auxin affected the development and yield of grapes (Vitis vinifera L.) grown in red yellow podzolic soil. A non-factorial totally randomized design with one factor (NAA concentration) was used in the study, with a block of 4 treatments and 3 repetitions. The varied NAA concentrations used in the treatment procedure included F0 (0 g L-1), F1 (2 g L-1), F2 (4 g L-1), and F3 (6 g L-1). The variables that were observed included the number of shoot bursts, the timing of leaf emergence, the number of sheet leaves, the length of the tendrils, and the proportion of live cuttings. ANOVA was used to tabulate and analyze observational data at a 5% level, and DMRT analysis was used to continue the analysis at the same level. According to the results, soaked NAA at a concentration of 0 g L-1 (S0) as the control treatment had the best results for the variable number of shoots and leaves, while a concentration of 2 g L-1 (S1) had the best results for the variable length of tendrils. However, soaked NAA had no significant impact on the variable when leaves emerged. Soaking auxin at the bottom of cuttings had no effect on shoot formation. Reduction of auxin due to defoliation can result in the expression of the isopentenyl-transferase (IPT) gene. Auxins, such as Indole-3-acetic acid (NAA), are usually involved in the regulation of root and leaf growth. If a plant has many leaves and few roots without the use of additional NAA or auxin, several factors may play a role, such as plant genetics, environmental conditions, and environmental stress. The use of additional NAA or auxin can explicitly affect the growth of roots and leaves. The survival percentage of cuttings is still low because it is influenced by the quality (material) of the cuttings, the age of the parent tree, growing media and water availability.